Answer:
x and y are 3 and -1 respectively
Step-by-step explanation:
let me help you with substitutuion method if it will help
let
2x - y = 7......................................equation 1
x + 3y =0..................................... equation2
from equation 2
x + 3y =0..................................... equation2
x = -3y........................................equation3
substitute for x = -3 in equation 1
2x - y = 7......................................equation 1
2(-3y) -y = 7
-6y-y = 7
-7y =7
divide both sides by -7
-7y/-7 =7/-7
y = -1
put the value of y=-1 in equation 3
x = -3y........................................equation3
x = -3(-1)
x= 3
therefore the value of x and y are 3 and -1 respectively